Demography, Human Capital Investment, and Lifetime Earnings for Women and Men - Joyce P. Jacobsen; Melanie Khamis; Mutlu Yuksel (Institute of Labor Economics (IZA), 2024)
Can the demographic trends of increased life expectancy and decreasing birth rates, along with the labor market patterns of returns to human capital investment and changes in real hourly earnings, account for changes in women's and men's lifetime earnings? Using a Vector Error Correction Model to analyze annual US CPS data from 1964 to 2019, we find patterns linking these factors and demonstrating that they have significant roles to women's lifetime earnings but not to men's. These findings are consistent with the convergence of gender earning gap has occurred mainly due to women's responses to changing demographic and socioeconomic factors.
Keywords: J3; J16; J24; 330; life expectancy; lifetime earnings; human capital investment; VECM